(untitled) (Jurnal Mekanikal, 2018)
Thermoacoustic refrigerator system generates cooling power from acoustic energy. Acoustic waves interact with stack plates in the resonator tube of a thermoacoustic refrigerator to induce a temperature difference the significance of which depends on the solid-fluid interactions. In this paper, the flow field at the end of the stack plates was investigated using Particle Image Velocimetry (PIV). Results were obtained from three stack configurations with different plate geometry. Effects of plate thickness and separation gap were determined by comparison of the velocity profile obtained from these three configurations. The ratio of separation gaps to viscous penetration depth was also determined to see the effect of separation gaps. And for plate thickness effects, Reynolds number for each configuration was calculated.